01 Major trauma triage tools study (MATTS) triage tools summary. Issue 10 (25th September 2020) - Holt, Christopher; Fuller, Gordon; Keating, Samuel; Turner, Janette; Irving, Andy; Herbert, Esther
Abstract : Introduction: The aim of this project is to identify major trauma triage tools currently in use by ambulance services in England, Wales and internationally and subsequently complete a detailed document analysis of these tools. The review will aim to detect the most commonly used predictors of major trauma whilst identifying the evidence behind them. Methods: A variety of triage tools used internationally were acquired through analysis of systematic reviews freely available on PubMed. The 46 identified tools included: 40 adult/general, 4 paediatric-specific and 2 geriatric-specific tools. Following the acquisition of all triage tools, they were analysed by diagnostic criteria and a detailed spreadsheet produced. Each row of the spreadsheet represented a different triage criterion and each cell was colour coded to suggest the correct course of action for patient management. Results: In total, 63 separate clinical features and triaging criteria were identified. These were categorised into five major groups (most common variables): Physiology (GCS, Low BP). Anatomy (Chest trauma, traumatic amputation). Mechanism of injury (Falls, high speed RTC). Modifiers for high risk groups (Age >55/65, pregnant) Time limit to the nearest MTC (>45 minutes). Additionally, crew concern is a potential predictor in 14 tools. Despite many tools using similar predictors, their respective predictor cut-points varied widely (e.g. from GCS ≤14 to <9). From the tools assessed, two basic tool structures were discerned: A flowchart style format (34 tools) A points-based scoring system (7 tools) Conclusions: The various major trauma triaging tools currently in use in the NHS and worldwide are highly varied. Although there are commonly used domains variable cut-points often varied. Given this significant difference between services' tools, and variability of clinician interpretation of those criteria, large variations in standards of major trauma triaging are likely.